PENGEMBANGAN LEMBAR KERJA PRAKTIKUM MATA PELAJARAN INSTALASI MOTOR LISTRIK KELAS XI TEKNIK INSTALASI TENAGA LISTRIK DI SMK NEGERI 1 LUBUK PAKAM - Nasution, Erwin Yusuf; Amin, Muhammad (Universitas Negeri Medan, 2023)
Abstract This research aims to: 1). To develop a practical worksheet for the electric motor installation subject class XI TITL at SMKN 1 Lubuk Pakam, 2). To test the feasibility of the practical worksheet for the electric motor installation subject that has been created for class Lubuk Pakam. This research methodology is research and development (Research & Development) with the Four-D Models development model. Four-D Models consists of 4 stages, namely: 1). Definition (Define), 2). Design, 3). Development (Develop), 4). Dissemination (Dissaminate). The Dissaminate stage was not carried out due to the narrow scope of the research. The instrument used is a non-test instrument in the form of a questionnaire with a Likert scale of 5 answer choices. The questionnaire was validated by an evaluation expert. Based on the results of the analysis and discussion, it is known that: 1) This development research produces learning resources in accordance with the syllabus, namely a practical worksheet consisting of 11 practical activities. 2) The level of suitability of the practicum worksheet is known from the assessment results of material experts, media experts, and the results of teacher and student responses. The results of material expert validation which included aspects of appropriateness of content, language, presentation and benefits achieved an average score of 116 with a percentage of 92.8% in the